Customer's operant resources effects on co-creation activities - Helena Alves; Jo\~ao J. M. Ferreira; Cristina Isabel Fernandes (Journal of Innovation & Knowledge (JIK), 2016)
This study analyses the influence of client operant resources, in the form of self-efficacy, bridging social capital and customer expertise, on co-creation activities with companies and the customer resulting perceived benefits. A quantitative study, based on a sample of 362 consumers was carried out to test a model that sets out the relationships among the variables in analysis. The results demonstrate not only how operant resources do effectively contribute towards explaining a certain percentage of the variation in customer co-creation activities, but also how this resources influence gets boosted by the efforts companies make to educate their customers. The results also show that co-creation with the firm enhances customer perceived benefits.
Keywords: M31; 650; Co-creation; Operant resources; Perceived benefits